Analisis risiko kesehatan akibat pajanan timbal (Pb) dalam biota laut pada masyarakat sekitar teluk Kendari (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: To understand the risk level of health problem because of the exposure to the lead metal found on fish and shellsfish consumed by community living around Kendari bay.Methods: This study was an analytical observational through a cross sectional study design by combining Environmental Health Risk Analysis (ARKL) and Environmental Health Epidemiology (EKL) approaches. Population of the study was community dwelling around Kendari bay and the sampling technique which qualified the proportional sampling criteria resulted 110 respondents. The marine biotas in this study were fish and shellfish from Kendari bay within 30 fish samples of 3 kind of most consumed fish and shellfish from 6 fishponds in Kendari bay. Measurement of lead content on fish and shellfish was made by Atomic Absorption Spectrometry (AAS).Results: The results of the study show that lead content on fish and shellfish were 0,0027-0,0095 mg/kg and 0,1026-0,1097 mg/kg respectively while intake rapidity of fish and shellfish 0,0051 mg/kg/day and 0,016 mg/kg/day respectively. The variables of lead content on fish and shellfish, intake rapidity, exposure frequency, exposure duration, body weight and intake level were used to draw the risk. Health risk level of consuming contaminated fish was 1.29 while the contaminated shellfish was 4.03. variables significantly associated with risk level of fish and shellfish consumption were lead content on fish, intake rapidity of shellfish, exposure frequency of fish and shellfish, exposure duration of fish and shellfish, and intake level of fish and shellfish. On the other hand, variables which were not associated with risk level of fish and shellfish consumption were lead content on shellfish, intake rapidity of fish and body weight.Conclusion: The community around Kendari Bay has a risk of health problems (RQ> 1) due to lead exposure, therefore it needs to be controlled.